Design of the Bank Customer Queue Application Based on the Switch and Sound Visualization - Yusuf, Yuhendra; Februanda, Sudindri Rahmad (Kopertis Wilayah X)
Activities or community needs the same individuals, especially in the public interest would lead to an activity that requires a service. Limitations of service will cause the queue. This sort of thing (queue), often found at the center of public interest, such as the line at the bank, bill payments (electricity, telephone, water), and so forth. Services at the bank, for example, customers who would require the service is to be in line to wait his turn to receive services. However, it must gain an awareness of costumer that public services should be optimal and primed with an adequate level of discipline from the culprit himself and cooperation among them. In order for such activities as expected, it is necessary to raise awareness in the culture culprit line up with the queue system, namely in the form of electronic line computer-based program. The device is designed in the form of software which is controlled by the switch, the line number is displayed on the monitor screen, and dialing by voice from the speaker. In this research, the Visual Basic 6.0 as an application developer, Ms. Access as DBMS, and Cool Edit Pro version 2.0 as a recorder and sound manipulator. Thus, this application can help a bank officer to call a customer in the queue to get the service, so that more optimal service to customers, excellent and efficient.